Organogenesis of Ileal Peyer's Patches Is Initiated Prenatally and Accelerated Postnatally With Comprehensive Proliferation of B Cells in Pigs - Furukawa, Mutsumi; Ito, Shun; Suzuki, Shunichi; Fuchimoto, Daiichiro; Onishi, Akira; Niimi, Kanae; Usami, Katsuki; Wu, Guoyao; Bazer, Fuller W.; Ogasawara, Kouetsu; Watanabe, Kouichi; Aso, Hisashi; et al. (Frontiers in Immunology, 2020)
Morphogenesis and differentiation of organs is required for subsequent functional maturation. The morphological features of Peyer’s patches vary among species. In pigs, they develop extensively in the ileum as ileal Peyer’s patches (IPPs). However, the role of IPPs in the porcine immune system remains to be elucidated because of a lack of complete understanding of IPP organogenesis. Results of the present study revealed that development of porcine IPPs is initiated prenatally between embryonic days 76 and 91 by B and T cells infiltrating the anlagen in a CXCL13- and CCL19-dependent manner. IPPs undergo further development postnatally by forming central, marginal, and subepithelial zones. Importantly, a large number of proliferating B cells and apoptotic cells are found in porcine IPPs postnatally, but not prenatally. Furthermore, the expression of IgM is extremely low in proliferating B cells in the marginal zone after birth, although B cells in IPPs express IgM before birth. Importantly, the cellular feature of IPPs differs from that of mesenteric lymph nodes (MLNs) where most B cells express IgM both prenatally and postnatally. Our findings suggest that IPPs (not MLNs) in postnatal pigs are involved in complementing functions of the primary lymphoid tissue that promotes the differentiation and maturation of B cells.